Agro-Economic Risks of Phytophthora and an Effective Biocontrol Approach - Mohamed Hussain Abdulkhair, Waleed; Mohamed Hussain Abdulkhair, Waleed (IntechOpen, 2021)
This book examines the risk of Phytophthora infection on different economic plants. It is divided into three sections that address the threats of Phytophthora infections to economic plants in Egypt and Ghana, the biocontrol of Phytophthora infections, and the prevalence and recognition of Phytophthora infection. This book discusses significant aspects of Phytophthora diseases as well as methods of their control to maintain sustainable agriculture and national economy. It is a valuable scientific resource for farmers, agriculturists, and other interested readers.
English
Keywords: Plant pathology & diseases